Evaluation of nutritional habits and the body mass index (bmi) of students of the University of the Third Age at the Koszalin University of Technology (Journal of Medical Science, 2016)
Introduction. Nutrition plays an important role in the elderly stage of life. A proper proportion of the individual nutritional ingredients in a diet may positively impact the ageing body. This positive influence consists in slowing down the undesired and unfavourable physiological alterations leading inevitably to the general weakness of the body. Aim. The aim of the study was to evaluate the nutritional habits and body mass indexes (BMI) of students of the University of the Third Age at the Koszalin University of Technology. Material and methods. A total of 189 people (34 men and 155 women) took part in the study in 2014, which involved a diagnostic survey and an evaluation of the nutritional state based on BMI. Results. Approximately 3/4 of the respondents were found to be overweight or obese. A large majority of them viewed their health status as good. The majority (70%) declared regularly eating 3–4 meals. Half of the respondents admitted eating snacks between meals. The majority of the respondents did not control the amount of calories consumed, but they reduced the consumption of cholesterol. About 3/4 of the respondents ate wholemeal bread and spread butter over it. They mainly used all-purpose oil for frying. About half of the respondents ate unprocessed fruit and vegetables every day and only 1/3 of them consumed milk and dairy products every day. About 3/4 of the respondents ate fish once a week. About 1/3 of the males and nearly half of the females ate vitamin and/or mineral supplements. About 3/4 of the respondents performed some physical exercise several times a week. Male and female respondents reported eating snacks between meals to a different extent. It was also found that the educational background significantly differentiated the amount of fruit and vegetables consumed as well as the time of the last meal of the day. The place of residence also significantly differentiates the number of meals and the extent to which the consumption of cholesterol is reduced. The respondents’ financial situation was also found to differentiate the form in which fruit are eaten. Conclusions. The findings suggest increased control of the amount of calories consumed, increased consumption of fruit and vegetables, dairy products and fish as well as the need for nutritional education.